Diseño de estrátegias competitivas para promover la exportación de cangrejo rojo hacia España - Gallegos Olaya, Karina Berenise (2017)
The present work originates from the problem actually faced by the crab associations of Churute mangroves in relation to the distribution of red crab, due to the sale of the product is only conducted at local level, and it is very necessary to promote the exportation of red crab to International markets despite the lack of adequate logistics and ignorance of the processes that must followed for an international certification; Therefore, the general objective is to design competitive strategies to promote the export of red crab, coming from the community organizations of the Churute mangroves. The research instruments used were the survey and observation made to artisanal fishermen of Churute mangrover, with questions that allowed us to obtain qualitative data of the activity, these data were tabulated in tables for analysis and evaluation. In the same way, in this research, the members of the associations of crabs of the Ecological Reserve Mangrove Churute are considered as a study population. Consequently, sampling was applied for convenience, the sample of the population was 425 collectors belonging to the 17 Associations, that is to say 25 members for each association, since it is required to obtain real information of all the associations that carry out this type of activity. After the analysis of the information obtained, a proposal will be designed that will serve to structure the strategies or competitive actions to be considered, in order to encourage the census associations to export the Ecuadorian product.